2023
DOI: 10.3390/math11153361
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Passenger Satisfaction and Reuse Intention with Monorail Services in Kuala Lumpur, Malaysia: A Hybrid SEM-ANN Approach

Ahmad Nazrul Hakimi Ibrahim,
Muhamad Nazri Borhan,
Muhamad Razuhanafi Mat Yazid
et al.

Abstract: This study employs the fundamental concept of the American Customer Satisfaction Index (ACSI) model to explore the factors influencing passengers’ satisfaction with monorail service in Kuala Lumpur, Malaysia and their reuse intention. The study tests the hypotheses on 417 monorail passengers using a hybrid structural equation modelling based on parameter estimation of partial least squares (PLS-SEM) and an artificial neural network (ANN) method to estimate the proposed model. The results showed that the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…These findings indicated that the proposed model explains 70.4% and 59.5% of passenger satisfaction and reuse intention, respectively. Both perceived quality and perceived value were found to significantly influence satisfaction, with the ANN identifying perceived quality as the most crucial predictor of satisfaction [51].…”
Section: Sem-annmentioning
confidence: 99%
“…These findings indicated that the proposed model explains 70.4% and 59.5% of passenger satisfaction and reuse intention, respectively. Both perceived quality and perceived value were found to significantly influence satisfaction, with the ANN identifying perceived quality as the most crucial predictor of satisfaction [51].…”
Section: Sem-annmentioning
confidence: 99%
“…It encompasses six variables: customer expectations, perceived quality, perceived value, customer satisfaction, customer complaints, and customer loyalty [13]. Building on the ACSI framework, Ibrahim et al utilized structural equation modeling (SEM) to explore factors influencing passengers' satisfaction with monorail services and their willingness to continue using the service [26]. Chen et al, based on ACSI, constructed a research model involving heritage perception value, perceived enjoyment, visit satisfaction, and post-visit behavioral intentions, validating it through SEM [27].…”
Section: Shared Micro-mobility Satisfactionmentioning
confidence: 99%